MLTI-06. BEVACIZUMAB VERSUS SURGICAL INTERVENTION FOR RADIATION NECROSIS IN PREVIOUSLY IRRADIATED BRAIN METASTASES. (12th August 2019) - Hong, Christopher; Sujijantarat, Nanthiya; Chiang, Veronica
Abstract: INTRODUCTION: Both medical management with bevacizumab and surgical management via craniotomy or more recently with laser interstitial thermal ablation (LITT) have been shown to be efficacious in the management of radiation necrosis (RN) after radiosurgery for brain metastases (BM). Indications for how to choose medical versus surgical management however remains unclear. METHODS: Single-institution chart review was performed of all patients with biopsy or radiographically confirmed RN after radiosurgery for BM between 2011 and 2017. Progression-free survival (PFS) and overall survival (OS) were compared between those treated using bevacizumab versus surgical intervention. RESULTS: 15 patients underwent craniotomy, 18 patients underwent LITT, and 18 patients were treated with bevacizumab. Those treated with bevacizumab had significantly higher number of regrowing lesions (n >1) at time of intervention (50.0%) versus those treated with surgery (15.2%) (p< 0.05). Likewise, pre-treatment KPS was lower in the bevacizumab cohort (median: 60) vs the surgery cohort (median: 90) (p< 0.05). Patients treated with bevacizumab demonstrated significantly decreased PFS (%PFS at 1-year 16.7% vs 86.7% and 87.8% for craniotomy and LITT, respectively; %PFS at 2-years 0% vs 86.7% and 73.2% for craniotomy and LITT, respectively, p < 0.05). Similar results were observed for OS (%OS at 1-year for bevacizumab 33.3% vs 93.3% and 73.8% for craniotomy and LITT, respectively; %OS at 2-years for bevacizumab 11.1% vs 64.6% and 63.2% for craniotomy and LITT, respectively, p< 0.05). CONCLUSIONS: Preliminary analysis shows that bevacizumab therapy in our institution is being chosen for patients with lower KPS and multiple regrowing lesions while surgical intervention is being chosen for patients with good KPS and single, symptomatic regrowing lesions. While the comparative outcomes after bevacizumab appear to be significantly worse than surgical management, it remains unknown if the difference is more related to its true efficacy or the significant discrepancy between the comparison groups.